2015
DOI: 10.3389/fpsyt.2015.00163
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profiles Correlated with Clinical and Behavioral Impairments in a Sample of Brazilian Children with Attention-Deficit Hyperactivity Disorder

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a complex neurodevelopmental disorder that implies several-step process, and there is no single test to diagnose both ADHD and associated comorbidities, such as oppositional-defiant disorder (ODD), anxiety disorder, depression, and certain types of learning disabilities. The purpose of the present study was to examine correlations between behavioral and clinical symptoms by administering an extensive neuropsychological battery to a sample of children and adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…However, when compared on internalizing disorders, the SpLD, ADHD and ASD groups reported higher levels of social withdrawal and anxiety/depression symptoms compared with the LD and TD groups. Although, studies comparing internalizing disorders in different NDDs are lacking, some researchers have highlighted the presence of emotional problems in ADHD, ASD and SpLD (Rizzutti et al, 2015). These findings suggest that child emotional and behavioral problems are significant sources of general parental stress.…”
Section: Discussionmentioning
confidence: 96%
“…However, when compared on internalizing disorders, the SpLD, ADHD and ASD groups reported higher levels of social withdrawal and anxiety/depression symptoms compared with the LD and TD groups. Although, studies comparing internalizing disorders in different NDDs are lacking, some researchers have highlighted the presence of emotional problems in ADHD, ASD and SpLD (Rizzutti et al, 2015). These findings suggest that child emotional and behavioral problems are significant sources of general parental stress.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that children with ADHD-PI perform worse than the controls and individuals with ADHD-C on the omission measure of the Conner's CPT [37,38]. Therefore, it has been suggested that the impairment of this ability is highly associated with the inattention criteria of the disorder [37,38]. In another CPT study, ADHD-PI individuals performed worse than typically developing controls not only in measures of selective attention (omissions), but also in other areas of attentional functioning such as the ability to maintain a consistent response time throughout the task, vigilance, processing speed, sustained attention, and inhibitory control [39].…”
Section: Behavioral Neurocognitive and Neuropsychological Impairmentsmentioning
confidence: 93%
“…A meta-analysis that included different CPT versions concluded that one of the most impaired measures in individuals with ADHD is the number of omissions, which indicates a deficit in the ability to respond to target stimuli (i.e., selective attention) [36]. Previous studies have shown that children with ADHD-PI perform worse than the controls and individuals with ADHD-C on the omission measure of the Conner's CPT [37,38]. Therefore, it has been suggested that the impairment of this ability is highly associated with the inattention criteria of the disorder [37,38].…”
Section: Behavioral Neurocognitive and Neuropsychological Impairmentsmentioning
confidence: 99%
“…The neuropsychological evaluation included the following: the children's intellectual level was tested using the abbreviated (estimated IQ) Wechsler Intelligence Scale for Children (WISC-III), the attention test using the Conners' Continuous Performance Test (CCPT), the Automated Working Memory Assessment (AWMA) test, and the BRIEF (Behaviour Rating Inventory of Executive Functions) test. The psychiatric interview included a Brazilian version of MTA-SNAP-IV, the Child Behaviour Checklist (CBCL), and the Brazilian version of the Conners Rating Scale (see Rizzutti et al, 2015-for more details)…”
Section: Participantsmentioning
confidence: 99%